Eco-Trap: Environmentally Friendly Mosquito Trap from Recycled Materials to Prevent Dengue Fever - Pramardika, Dhito Dwi; Kasaluhe, Meityn Disye; Patras, Mareike Doherty; Pangandaheng, Nansy Delia; Wuaten, Grace Angel; Lalombo, Agneta Sartika (Universitas Putra Indonesia YPTK Padang, 2025)
This community service program developed eco-trap innovation as a sustainable solution for mosquito vector control at SMA Negeri 3 Tahuna Barat. This initiative has addressed environmental health issues caused by mosquito breeding and the accumulation of plastic waste in the school environment. The implemented method combines a participatory educational approach with practical training in making mosquito traps from used plastic bottles. A total of 54 students participated in the program, which was conducted in September 2025. Evaluation using the pretest-posttest and Wilcoxon statistical analysis showed a significant increase in participants’ knowledge (Z=-5.689, p=0.000) and attitude (Z=-4.534, p=0.000). This program not only succeeded in enhancing students’ capacity for environmentally friendly vector control but also instilled the principles of a circular economy through the use of recycled materials. The results of the activity demonstrate the effectiveness of participatory environmental education in building ecological awareness while supporting the achievement of sustainable development goals in health and education.